Legal Politics of the Reform of Law No. 9 of 1961 on the Collection of Money and Goods Related to Philanthropic Governance in Indonesia - Rahman, Nur Ali (Riwayat: Educational Journal of History and Humanities, 2024)
This study aims to analyze the legal politics behind the reform of Law No. 9 of 1961 concerning Collection of Money and Goods Related to Philanthropic Governance in Indonesia. Philanthropy has an essential role in advancing society and improving social welfare. However, regulations governing philanthropy in Indonesia are still relatively old-fashioned and have not accommodated the dynamics and complexities of todays philanthropic practices. This study uses a normative legal research method with a juridical-critical approach. The research results show that Law No. 9 of 1961 has not been able to answer the challenges and needs of todays philanthropy in Indonesia. Lack of assertiveness, limited scope, and underdevelopment of administrative requirements are obstacles to effective philanthropic governance. In addition, there is an imbalance of interests between philanthropic parties, beneficiaries, and the government, influencing the implementation and renewal of philanthropic policies. This research recommends law reform to improve philanthropic governance in Indonesia. Revision of Law No. 9 of 1961 must accommodate diverse philanthropic practices, emphasize corporate social responsibility, strengthen oversight mechanisms, and promote transparency and accountability in philanthropic practices. In addition, involving relevant actors such as philanthropic institutions, beneficiaries, government, and civil society in the renewal process is essential to reaching sustainable and inclusive agreements. It is hoped that the results of this research can provide valuable insights and recommendations for policymakers, legal practitioners, and related stakeholders to encourage the reform of Law No. 9 of 1961 to create more effective and sustainable philanthropic governance in Indonesi